Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/ja405395z
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Kinetic Study of Cleavage of the N–O Bond of N-Oxides by a Vanadium(III) Complex: Enhanced Oxygen Atom Transfer Reaction Rates for Adducts of Nitrous Oxide and Mesityl Nitrile Oxide

Abstract: Thermodynamic, kinetic, and computational studies are reported for oxygen atom transfer (OAT) to the complex V(N[t-Bu]Ar)3 (Ar = 3,5-C6H3Me2, 1) from compounds containing N-O bonds with a range of BDEs spanning nearly 100 kcal mol(-1): PhNO (108) > SIPr/MesCNO (75) > PyO (63) > IPr/N2O (62) > MesCNO (53) > N2O (40) > dbabhNO (10) (Mes = mesityl; SIPr = 1,3-bis(diisopropyl)phenylimidazolin-2-ylidene; Py = pyridine; IPr = 1,3-bis(diisopropyl)phenylimidazol-2-ylidene; dbabh = 2,3:5,6-dibenzo-7-azabicyclo[2.2.1]he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 53 publications
(70 reference statements)
4
36
0
Order By: Relevance
“…5 [10,12] By drawing parallels with the reaction of aneutral rhodium PNP analogue with N 2 O, where formation of ad iscrete adduct is inferred but not experimentally corroborated, we suggest 2 decomposes by abimetallic oxygen atom transfer mechanism that is initiated by dissociation of N 2 Oa nd proceeds via {(pincer)Rh II -N = N-O-Rh II (pincer)} 2+ . [9,13] Consistent with this assertion, enhanced solution stability was observed under aN 2 Oa tmosphere (2 %/30 %d ecomposition of 2a/b after 24 h).…”
mentioning
confidence: 55%
“…5 [10,12] By drawing parallels with the reaction of aneutral rhodium PNP analogue with N 2 O, where formation of ad iscrete adduct is inferred but not experimentally corroborated, we suggest 2 decomposes by abimetallic oxygen atom transfer mechanism that is initiated by dissociation of N 2 Oa nd proceeds via {(pincer)Rh II -N = N-O-Rh II (pincer)} 2+ . [9,13] Consistent with this assertion, enhanced solution stability was observed under aN 2 Oa tmosphere (2 %/30 %d ecomposition of 2a/b after 24 h).…”
mentioning
confidence: 55%
“…34 Oxygen atom transfer was also demonstrated for cyclopentadienyl complexes of vanadium, 35 tantalum, 36 zirconium, 37 and hafnium. 44 At low temperature, however, an overall second order was observed. The Mindiola group has shown that vanadium 39 and titanium 40 alkyl complexes can be oxidized with N 2 O to give complexes with terminal oxo ligands.…”
Section: N O As O-atom Donormentioning
confidence: 97%
“…Elimination of arenes resulting in group transfer has been employed to deliver a variety of moieties, including N − ,,, NH, CH, NCN,, O, PCH, and P 2 ,. Recently, ClPA was employed to transfer P + to an anionic vanadium nitride to generate the pnictogen–pnictogen linkage in a transient P−N complex .…”
Section: Figurementioning
confidence: 99%
“…Monometallic four‐electron oxidative addition is known, but is limited to the insertion of metal fragments into unsaturated C=O, C=S, C=N,, and N=N bonds. Group transfer through the elimination of a single arene equivalent more typically results in two‐electron processes,,,,, although four‐electron reactivity has been demonstrated when employing two metal centers as group or atom acceptors . The hapticity change of the metal–arene interaction from η 6 ( 1 ) to η 2 ( 2 ) facilitates this multi‐electron transformation; the d orbitals engaging in Mo−arene π bonding in the low‐valent starting material are liberated to form the Mo−P bonds in the product.…”
Section: Figurementioning
confidence: 99%